Studies on the prevalence, diagnostic algorithm and antimicrobial drug sensitivity of Streptococcus suis isolates from industrially reared pigs - V. Galeva; L. Ivanov; V. Urumova (Bulgarian Journal of Veterinary Medicine, 2025)
From January 2022 to September 2022, a total of 58 swab samples were collected from an industrial pig farm located in South Bulgaria  54 samples from vaginal/cervical discharge of breeding sows and nasal mucosa of neonatal piglets (44 samples from sexually mature sows; 10 samples from suck-ling piglets) and 4 tonsillar samples from dead or culled pigs. Out of the 58 swabs, 13 (22.4%) Strep-tococcus suis strains were isolated: 9 (20.4%) isolates from vaginal/cervical discharge of sows, 1 (10%) isolate from the nasal mucosa of a suckling piglet, and 2 strains (50%) from tonsils of dead or culled sows. One isolate (2.3%) from the vaginal/cervical discharge of breeding sows was deter-mined as serotype 2-1/2. Also, 15 strains (34.1%) identified as Streptococcus equi subsp. zooepi-demicus were isolated from vaginal/cervical discharge of breeding sows, and one tonsillar isolate (25%) was identified as Streptococcus dysgalactiae subsp. equisimilis. The resistant Streptococcus suis strains to tetracycline (91.7%), florphenicol (91.7%), enrofloxacin (91.7%) and colistin (75%) were more prevalent among streptococcal isolates. A multiresistant pattern including the nine tested antimicrobial drugs was demonstrated for three Streptococcus equi subsp. zooepidemicus strains (20%) isolated from vaginal/cervical discharge of breeding sows.